Directing intracellular supramolecular assembly with N-heteroaromatic quaterthiophene analogues. Issue 1 (December 2017) - Ng, David; Vill, Roman; Wu, Yuzhou; Koynov, Kaloian; Tokura, Yu; Liu, Weina; Sihler, Susanne; Kreyes, Andreas; Ritz, Sandra; Barth, Holger; Ziener, Ulrich; Weil, Tanja
Abstract Self-assembly in situ, where synthetic molecules are programmed to organize in a specific and complex environment i.e., within living cells, can be a unique strategy to influence cellular functions. Here we present a small series of rationally designed oligothiophene analogues that specifically target, locate and dynamically self-report their supramolecular behavior within the confinement of a cell. Through the recognition of the terminal alkyl substituent and the amphiphilic pyridine motif, we show that the cell provides different complementary pathways for self-assembly that can be traced easily with fluorescence microscopy as their molecular organization emits in distinct fluorescent bands. Importantly, the control and induction of both forms are achieved by time, temperature and the use of the intracellular transport inhibitor, bafilomycin A1. We showcase the importance of both intrinsic (cell) and extrinsic (stimulus) factors for self-organization and the potential of such a platform toward developing synthetic functional components within living cells. Self-assembly of synthetic molecules in living cells can influence cell function, but is extremely challenging due to the complex environment of cells. Here the authors report the self-assembly of small organic molecules that locate, target and self-report their supramolecular behavior in living cells.